Muscle Thickness and Echogenicity Measured by Ultrasound Could Detect Local Sarcopenia and Malnutrition in Older Patients Hospitalized for Hip Fracture - Sanz-Paris, Alejandro; González-Fernandez, Mikel; Hueso-Del Río, Luis Enrique; Ferrer-Lahuerta, Eduardo; Monge-Vazquez, Alejandra; Losfablos-Callau, Francisco; Sanclemente-Hernández, Teresa; Sanz-Arque, Alejandro; Arbones-Mainar, Jose Miguel (Nutrients, 2021)
Background: The aim of this work was to assess whether the muscle thickness and echogenicity were associated with dysphagia, malnutrition, sarcopenia, and functional capacity in acute hospital admission for a hip fracture. Methods: Observational study that assessed nutritional status by Global Leadership Initiative on Malnutrition, risk of dysphagia and sarcopenia by European Working Group on Sarcopenia in Older People and Barthel functional index. We measured muscle thickness and echogenicity of masseter, bicipital, and quadriceps rectus femoris (RF) and vastus intermedius (VI) by ultrasound. Results: One hundred and one patients were included in the study (29.7% sarcopenia and 43.8% malnutrition). Logistic regression models adjusted for age, sex, and body mass index showed an inverse association of the masseter thickness with both sarcopenia (OR: 0.56) and malnutrition (OR: 0.38) and quadriceps with sarcopenia (OR: 0.74). In addition, patients at high risk of dysphagia had lower masseter thickness (p: 0.0001) while patients able to self-feeding had thicker biceps (p: 0.002) and individuals with mobility on level surfaces higher thickness of biceps (p: 0.008) and quadriceps (p: 0.04). Conclusion: Thickness of the masseter was associated with risk of dysphagia, biceps with the ability to self-feed, and that of the quadriceps RF-VI with mobility.